2004
DOI: 10.2527/2004.8292579x
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth and nitrogen balance in grower-finisher pigs1

Abstract: Sixteen castrated male pigs (averaging 21.2 +/- 4.9 kg) were used in two trials to investigate the effect of dietary amino acid content during the grower phase on growth performance and N balance. In each trial, pigs were assigned randomly to corn-soybean meal grower diets formulated to contain 5.0 or 11.0 g lysine/kg (as-fed basis). Common Finisher 1 and 2 diets were offered when pigs reached 51.2 +/- 3.3 and 79.5 +/- 3.4 kg, respectively. Pigs were placed in metabolism crates for a 9-d period during each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
49
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 28 publications
11
49
4
2
Order By: Relevance
“…The present study demonstrates for the first time that changing dietary levels of a single essential amino acid from deficient to sufficient, in a diet containing adequate amounts of other nutrients and energy, induces compensatory growth in growing rats. In previous reports, although laboratory animals and livestock showed compensatory growth with sufficient intake of protein or amino acids, the tested diets used in those experiments were deficient in multiple amino acids, but not in a single amino acid (7,8). Moreover, in these experiments, the terms of compensatory phase was long as 1 mo and the magnitudes of deficiency were severe.…”
Section: Discussionmentioning
confidence: 90%
“…The present study demonstrates for the first time that changing dietary levels of a single essential amino acid from deficient to sufficient, in a diet containing adequate amounts of other nutrients and energy, induces compensatory growth in growing rats. In previous reports, although laboratory animals and livestock showed compensatory growth with sufficient intake of protein or amino acids, the tested diets used in those experiments were deficient in multiple amino acids, but not in a single amino acid (7,8). Moreover, in these experiments, the terms of compensatory phase was long as 1 mo and the magnitudes of deficiency were severe.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Fabian et al (2004) reported that pigs subjected to early dietary amino acid restrictions can reduce nitrogen excretion during both the restriction and subsequent phases, thus exhibiting compensatory nitrogen retention during the realimentation phase. It has been suggested (Fabian et al 2004) that the compensatory nitrogen retention might be responsible for compensatory growth responses in terms of both growth performance and body composition (e.g., Chiba 1994Chiba , 1995Fabian et al 2002), the efficiency of feed or nutrient utilization (e.g., Valaja et al 1992;Chiba et al 2002;Fabian et al 2002), or lean Chiba et al (2002). y LysI, daily lysine intake [not reported by Chiba et al (2002)]; LMA, carcass longissimus muscle area.…”
Section: Discussionmentioning
confidence: 99%
“…If pigs have the ability to achieve compensatory growth (e.g., Robinson 1964;Wahlstrom and Libal 1983;Critser et al 1995) regardless of the genotype (de Greef et al 1992;Chiba et al 1999;Fabian et al 2002), it can reduce feed costs, as well as excretion of unused nutrients, during the restriction phase. Furthermore, restricted pigs may grow faster and more efficiently during the realimentation phase (Prince et al 1983;Valaja et al 1992;Chiba et al 2002), thus reducing the excretion of unused nutrients further (Fabian et al 2004). Compensatory growth, therefore, can have a positive impact not only on the overall efficiency of pig production but also on the environment.…”
mentioning
confidence: 99%
“…Moreover, the experimental diet exhibited no significant effect on the N retention of the Piétrain sired boars used in Study 1, whereas the Duroc sired boars used in Study 2 showed a significantly increased N retention for pigs received Diet 2 or 3 compared to those that consumed Diet 1. Several authors mentioned higher N retention for pigs fed diets with increased AA concentrations (5.0 g lysine/kg and 11.0 g lysine/kg) in the diets, respectively several diets, with increasing AA levels (8.1 till 13.1 g lysine/kg) during the growth period (Fabian et al 2004, O'Connell et al 2006. Reynolds & O'Doherty (2006) also described that the pigs fed a high lysine level (12.5 g/kg) had a higher (P<0.05) N retention than pigs fed diets with lower lysine concentrations (10.5 till 8.5 g lysine/kg).…”
Section: Discussionmentioning
confidence: 99%